Essays On Political Education - Crick, Bernard; Heater, Derek (Routledge Library Editions: Education, 1977)
In the 1960s and 1970s there was a remarkable development of interest in political education not only in Britain but also in other countries, namely the USA, Germany and Australia. This volume provides scholars and teachers in this field with a picture of British work in the area of political education.